PENGARUH PENDAPATAN ASLI DAERAH (PAD), DANA ALOKASI UMUM (DAU), DANA ALOKASI KHUSUS (DAK) TERHADAP TINGKAT KEMANDIRIAN DAERAH PADA PEMERINTAH DAERAH KABUPATEN KOTA DI PROVINSI SULAWESI TENGAH - Kustianingsih, Nurafni; Muslimin, Muslimin; Kahar, Abdul (Katalogis, 2018)
This study aims to determinate and analyze simultanoes and partia influeence of local revenues, general allocation funds, and special allocation funds on districts/towns independency level in central sulawesi province. Sample consist of 11 district/towns in Central Sulawesi Province that selected through purposive sampling method. Method of study in descriptive verificative and analyzed with multiple liner regressions. The result shows that local revenues, general allocation fund simultaneously have significant and positive influence on district/towns independency level in Central Sulawesi Province; partialy, local revenues has significant and positive influence on districts/towns independency level in Central Sulawesi Province; partially, general allocation funds and special allocaqtion funds have significant and negative influence on district/towns independency level in Central Sulawesi Province.